Assessment of the exclusion potential of suspects by using microbial signature in sexual assault cases: A scenario-based experimental study - Karadayi, Sukriye; Arasoglu, Tulin; Akmayan, Ilkgul; Karadayi, Beytullah (ELSEVIER IRELAND LTD, 2021)
Sexual assault offences are one of the most serious crimes committed against a person, typically rank only second to homicide, and represent one of the major challenges in forensic sciences. In some cases of sexual assault, there may be more than one suspect and the analysis of the biological evidence with currently available methods such as human DNA analysis may not yield results. In this study using the designed experimental model (with different experimental scenarios that can be designed), it was aimed to investigate the effectiveness of the microbiome profile for the identification of the offender by comparing the microbiome structures of the suspects' saliva samples with the mixed samples on the victim (saliva transmitted on breast skin) within the first 48 h after a sexual assault. For this purpose, a total of 44 samples was collected from four healthy females and four healthy males aged 20-50 years. Microbiome profiles of 44 samples in four groups containing saliva, breast skin and mixed samples were determined with the IIlumina HiSeq platform. Differentiation between samples were calculated by beta-diversity analysis methods by using QIIME software (v1.80). To compare the differentiation among samples and groups, unweighted UniFrac distance values were applied. Eight dominant microbial genera accounted for 86.15% of the total bacterial population in male saliva samples and were composed of Fusobacterium, Haemophilus, Neisseria, Porphyromonas, Prevotella, Rothia, Streptococcus and Veillonella. These genera constituted 76.72% of the bacterial population in mixed samples, whereas they constituted 34.40% of the bacterial population in the breast skin samples. Results of this study show that bacterial DNA in saliva can be recovered from saliva transmitted breast skin within at least 48 h. In conclusion, it has been found that examination of the microbiota of the saliva transmitted to breast skin of a sexual assault victim as a forensic tool may have the potential to determine the offender of the incident among the suspects or to reduce the number of suspects. Supporting the results of this study with further studies using parameters such as different case models, different body regions, larger time periods and a higher number of participants will be beneficial to draw accurate conclusion of the judicial case. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Forensic microbiome; Sexual assault; Metagenomic; Microbial signatures; Breast skin and saliva samples; HUMAN SKIN; IDENTIFICATION; DIVERSITY; INDIVIDUALS; PATTERNS; MARKERS; DNA; Legal Medicine